Cytotoxic Activity of Eugenia polyantha Wight Leaves Extract, Purified Extract and Ethyl Acetate Fraction in T47D and Determination of Flavonoid Levels - Hidayati, Devi Nisa; Parusiza, Intan Meyta; Fauzizah, Nisa (Indonesian Journal of Chemical Science, 2022)
Breast cancer is one of the cancers with the highest incidence in women in Indonesia. Old bay leaf extract (Eugenia polyantha Wight) has been proven to contain flavonoids so that it has anticancer activity. The flavonoid compounds can be extracted with ethyl acetate as solvent. The purpose of this study was to determine the cytotoxic activity of extracts, purified extracts, and the ethyl acetate fraction of old bay leaves against T47D breast cancer cells and to investigate their total flavonoid levels. Extraction using maceration method on old Eugenia polyantha Wight powder with methanol solvent, followed by purification and fractionation using ethyl acetate solvent. Cytotoxic activity using the MTT assay method. T47D cells were treated with each test sample with concentration of 31.25; 62.5; 125; 250; 500 and 1000 µg/mL. The absorbance was seen with an ELISA reader and viability cells (%) were calculated to obtain IC50. Determination of flavonoid levels with quercetin and analyzed by UV-Visible spectrophotometry. The result showed that the extract, purified extract, and ethyl acetate fraction of old Eugenia polyantha Wight had a cytotoxic activity with IC50 values of 798.808 g/mL; 593.826 g/mL, and 171.946 g/mL, respectively. Meanwhile, the flavonoid levels were 1.60 mgQE/g, 9.3 mgQE/g, and 5.27 mgQE/g, respectively.